How Prospective Mathematics Teachers Do Computational Thinking (CT) Task? : An Analysis Of CT Prior Knowledge - Sari, Dwi Maulida; Suhendra; Elah Nurlaelah (Hipotenusa: Journal of Mathematical Society, 2024)
The purpose of writing this article is to find out about the initial Computational Thinking ability of prospective mathematics teacher students. This is because the 21st century demands changes in human resources (HR) to be more superior and competitive. Excellent and competitive human resources require the ability of Computational Thinking (CT), because it can help a person develop critical, creative, and analytical thinking skills in solving complex problems, both in the context of computing and everyday life. Improving the quality of human resources cannot be separated from the implementation of education in preparing this requires an educator who has the capability to be able to provide good and effective learning. Students that are expected to become professional teachers in the field of mathematics education in the future must have good CT ability. So, the condition of prior CT ability of Tadris Mathematics Education students as mathematics teacher candidates needs to be investigated. The method used in this article is qualitative research with a descriptive approach, with the aim of describing the prior CT abilities of prospective mathematics teachers, namely Tadris Mathematics Education students. Based on the analysis of the answers and further interviews of students which are prospective mathematics teachers, it is concluded that the CT ability is still low and not good, especially in the indicators of pattern recognition, algorithms, abstraction and generalization. So it is necessary to develop a learning or approach that can improve the CT ability of prospective mathematics teachers.